2018
DOI: 10.1111/1556-4029.13739
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Approaches to the Backlog of Untested Sexual Assault Kits in the U.S.A.

Abstract: Motivated by the debate over how to deal with the huge backlog of untested sexual assault kits in the U.S.A., we construct and analyze a mathematical model that predicts the expected number of hits (i.e., a new DNA profile matches a DNA sample in the criminal database) as a function of both the proportion of the backlog that is tested and whether the victim-offender relationship is used to prioritize the kits that are tested. Refining the results in Ref. (Criminol Public Policy, 2016, 15, 555), we use data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 24 publications
0
41
0
Order By: Relevance
“…14). We also note that the CODIS yield under full testing in Detroit, MI (3) was 723 1468 = 0.493 (5), and the CODIS yield in the Manhattan District Attorney's Office's Sexual Assault Kit backlog Elimination Grant Program, which allowed one random sample from a SAK to be tested, was less than 18,803 55,252 = 0.340, which is the mean number of CODIS entries per SAK. While these two quantities are not inconsistent with our findings, the CODIS yield in ref.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…14). We also note that the CODIS yield under full testing in Detroit, MI (3) was 723 1468 = 0.493 (5), and the CODIS yield in the Manhattan District Attorney's Office's Sexual Assault Kit backlog Elimination Grant Program, which allowed one random sample from a SAK to be tested, was less than 18,803 55,252 = 0.340, which is the mean number of CODIS entries per SAK. While these two quantities are not inconsistent with our findings, the CODIS yield in ref.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, the benefit-tocost ratio is somewhat similar for full testing (which is estimated to be 81.34 in ref. 5) and the SAFE policy (estimated to be 91.77), although the former policy more than doubles the CODIS yield; i.e., the additional effectiveness achieved by testing only samples deemed probative by SAFEs is mostly offset by the lack of economies of scale associated with testing so few samples per kit. Taken together, these results provide strong support for testing all samples in a SAK, as is currently done in the San Francisco Police Department Criminalistics Laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings from the validation study also hold true in a previous study that suggested a relationship did not exist between the number of years a sexual assault kit spent in evidence storage and the probability that the kit contained a probative DNA profile . Furthermore, a recent mathematical modeling of the untested backlog of SAKs in the United States found that testing stored SAKs was a cost‐effective approach to averting the overall cost of sexual assaults .…”
Section: Discussionmentioning
confidence: 99%